Design, Synthesis, Characterization and Bioactivity Evaluation of New Symmetric Disulfonamides and Dicarbamates of 4,4'-Oxydianiline - Hari Babu, Pulluru; Naga Raju, Chamarthi; Narasimhulu Chetty, A.; V. Chalapathi, P.; Sreenivasa Murthy, P.; Nagalakshmi Devamma, M. (Anti-Infective Agents, 2017)
Background: A series of new symmetric disulfonamide and dicarbamate derivatives of 4,4#136;-oxydianiline were designed and synthesized in a simple method. These compounds were characterized by IR, 1H, 13C-NMR, mass spectral data and elemental analysis. Method: The compounds were screened for their in vitro antibacterial and antifungal activities against various pathogenic organisms. Among the title compounds 10f, 10a and 10h showed promising antibacterial activity and 10g, 10d and 10a showed good antifungal activity. Conclusion: The results also emphasized that the disulfonamide derivatives were better antibacterial agents than the corresponding dicarbamate derivatives.
Keywords: 4' -oxydianiline